Development of gallbladder cancer during follow-up of pancreaticobiliary maljunction: a report of two cases. Issue 12 (30th December 2022) - Aota, Takanori; Tanaka, Shogo; Takemura, Shigekazu; Amano, Ryosuke; Kimura, Kenjiro; Shinkawa, Hiroji; Ohira, Go; Nishio, Kohei; Ishizawa, Takeaki; Kubo, Shoji
Abstract: Pancreaticobiliary maljunction (PBM) is a congenital malformation. The reflux of pancreatic juice into the biliary tract caused by PBM plays a significant role in the development of biliary tract cancers (BTCs), such as gallbladder cancer and cholangiocarcinoma. Previous studies have demonstrated a high incidence of BTC in patients with PBM. However, there are only a few reports of patients who developed BTC after a diagnosis of PBM. We report the cases of two patients who developed gallbladder cancer after being diagnosed with PBM. They had refused treatment and were being managed with follow-up observation alone after the diagnosis of PBM and developed gallbladder cancer after several years of observation. Thus, surgical treatment should be recommended for all patients with PBM in order to prevent the development of BTC. Moreover, long-term, close, regular follow-up is necessary to facilitate the early diagnosis of subsequent BTC in patients with untreated PBM.